Antisense RNA: Function and Fate of Duplex RNA in Cells of Higher Eukaryotes - Kumar, Madhur (American Society for Microbiology, 1998)
There is ample evidence that cells of higher eukaryotes express double-stranded RNA molecules (dsRNAs) either naturally or as the result of viral infection or aberrant, bidirectional transcriptional readthrough. These duplex molecules can exist in either the cytoplasmic or nuclear compartments. Cells have evolved distinct ways of responding to dsRNAs, depending on the nature and location of the duplexes. Since dsRNA molecules are not thought to exist naturally within the cytoplasm, dsRNA in this compartment is most often associated with viral infections. Cells have evolved defensive strategies against such molecules, primarily involving the interferon response pathway. Nuclear dsRNA, however, does not induce interferons and may play an important posttranscriptional regulatory role. Nuclear dsRNA appears to be the substrate for enzymes which deaminate adenosine residues to inosine residues within the polynucleotide structure, resulting in partial or full unwinding. Extensively modified RNAs are either rapidly degraded or retained within the nucleus, whereas transcripts with few modifications may be transported to the cytoplasm, where they serve to produce altered proteins. This review summarizes our current knowledge about the function and fate of dsRNA in cells of higher eukaryotes and its potential manipulation as a research and therapeutic tool.